Ferramenta para análise de regras de firewall - Guerra, Matheus Sapia (2019)
Having a firewall on your network is not necessarily synonymous with security. Implementing and maintaining firewalls is a complex task that requires minimal knowledge of computer networking and cybersecurity concepts. In addition, the firewall configuration process typically does not provide administrators with feedback about the correctness of created and deployed rules that can make the network susceptible to cyber attacks. Thus, to know about the effectiveness of the rules, many tests with the rules implemented in the firewalls are necessary. However, to perform these tests there is a need to create different network scenarios for conducting experiments. Because of this also, practical activities designed to teach about the operation and configuration of firewalls, are complex to be performed, due to lack of computational resources and consequently, the performance of these activities is compromised. In this context, the objective of this work was to develop a tool that helps network administrators, students or enthusiasts to test and configure firewalls effectively and practically. In addition to helping to detect potential configuration errors, it presents the user with a simple, intuitive and informative interface. In order to verify the efficiency of the proposed tool, load experiments were carried out to prove that its use will not be limited, allowing the user to develop different network scenarios, together with the configuration of firewall rules at a runtime that allows them to be used. makes it possible to use the tool. The difference between this work and other tools is that it uses the approach of simulating network services and testing firewalls. Thus, it is possible not only to administer, but also to learn how to use firewalls, configuring them efficiently and accurately. Providing computer networks with security and usability.